ʺNew eugenics", gender and sexuality: a global perspective on reproductive politics and sex education in Cold War Europe - Varsa, Eszter; Szikra, Dorottya (The history of the family, 2020)
The article addresses reproductive politics and sex education in Cold War Europe in light of novel historical research. Integrating sex education into reproductive politics it delineates four hitherto little discussed conceptual and topical areas in the field, and points to possibilities for further research. Most importantly, the article places the globalized character of post-World War II reproductive politics at the center of historical investigation. It sheds light on the position of (state socialist) Europe in the global processes that shaped fertility- and sexuality-related discourses, policies and practices during the Cold War, and the role of transnational agencies. Secondly, the article highlights the postwar persistence of eugenic thought in reproductive politics, still largely missing especially from the historiography of state socialist countries. It points to the ways in which “new eugenics” is related to its earlier manifestations in Europe as well as how it adapted to state socialist contexts. Third, the article discusses the important contribution of gender and intersectional scholarship on the history of sex education and reproductive politics in Europe to the social and welfare history of the region. Finally, the article pays specific attention to the role of the Catholic Church in the former “Eastern bloc.” It underlines how reproductive issues enabled the Church to affect politics and engage with the state in heterogeneous ways beyond opposition. The article suggests that further historical analysis could importantly contribute to a better understanding of the present rise of populist right-wing discussion focused on the demise of the traditional family and the fall of birth rates.
Gesehen am 02.02.2021